The Mediating Role of Risk Management in the Relationship Between Independent Commissioners, Audit Committee, and Firm Value - Ana Mardiana; Suwandy; Anthony Holly; Gafrilla Jeconia Antou (www.amertainstitute.com, 2025)
The aim of this research is to examine the mediating role of risk management on the relationship between independent commissioners and audit committees on firm value. This study uses agency theory and stakeholder theory to explain the relationship between variables. This research uses a purposive sampling method in selecting samples. The data source in this research is the annual reports of non-financial companies listed on the Indonesia Stock Exchange (BEI) for the period 2020 to 2024. The total sample that meets the criteria is 155 non-financial companies. The data collection method used is the observation method. The results of this research show that independent commissioners have a positive and insignificant influence on risk management. The audit committee has a positive and significant influence on risk management. Risk management has a positive and insignificant influence on firm value. Independent commissioners have a positive and significant influence on firm value. The audit committee has a negative and insignificant influence on firm value. Risk management does not mediate the influence of independent commissioners on firm value. Risk management does not mediate the influence of the audit committee on firm value.